2(6s+11)-6s=2(3s+2)-9

Simple and best practice solution for 2(6s+11)-6s=2(3s+2)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6s+11)-6s=2(3s+2)-9 equation:



2(6s+11)-6s=2(3s+2)-9
We move all terms to the left:
2(6s+11)-6s-(2(3s+2)-9)=0
We add all the numbers together, and all the variables
-6s+2(6s+11)-(2(3s+2)-9)=0
We multiply parentheses
-6s+12s-(2(3s+2)-9)+22=0
We calculate terms in parentheses: -(2(3s+2)-9), so:
2(3s+2)-9
We multiply parentheses
6s+4-9
We add all the numbers together, and all the variables
6s-5
Back to the equation:
-(6s-5)
We add all the numbers together, and all the variables
6s-(6s-5)+22=0
We get rid of parentheses
6s-6s+5+22=0
We add all the numbers together, and all the variables
27!=0
There is no solution for this equation

See similar equations:

| -4=-5+n/14= | | -10=10(4+v)= | | -6(2n+4)-4=-112 | | 34+n+12=78-7 | | -162=-92+v)= | | -8/5x=3/4 | | u/5=-66 | | -37+x=26 | | (6x+5)/(9x+8)=0 | | 0=-9(b+5)= | | -48=-2x-6(-x+16) | | -u/7=49 | | 7x-7=-14= | | -10x-13=-7x+26 | | -10(-9+a)=-30= | | 0=100x-x^2 | | 1/3h=-3h= | | 1+5p=-44= | | 4x+4(-5x-19)=172 | | 12=-4(-6x-312) | | 2314=k+716 | | 2-1/2x=12 | | 25+x/2=31.5 | | 13=9+r/2= | | 40=2l+2(35) | | -38=-4+2n= | | 35=1-2a= | | (6x+5)(9x+8)=0 | | 2(6x+24)=2(7x+14 | | 32+a=-32 | | -7=-9+n/8= | | v-42=98-9v |

Equations solver categories